Circumstances in a young German cohort with sudden cardiac arrest: systematic insights and implications : letter to the editors - Kreimer, Fabienne; Thiesing, Pia; Akın, Ibrahim; Tiesmeier, Jens; Milting, Hendrik; Mügge, Andreas; Hamdani, Nazha; Aweimer, Assem; El-Battrawy, Ibrahim (Clinical research in cardiology, 2025)
Introduction Data on circumstances of sudden cardiac arrest (SCA) in Germany are limited. The present study aimed to investigate systematically the current pre- and in-hospital circumstances of a SCA cohort at young age (65 years or younger) in Germany. Methods In the period from 2010 to 2021, we enrolled 191 consecutive patients with SCA at a university hospital in the Ruhr area, Germany. Clinical baseline characteristics and cardiopulmonary resuscitation (CPR) data were assessed. Results A total of 191 patients (median age: 56 years (ranging from 16 to 65 years); 82% males) were included. The median duration of hospitalization was nine days. 97 patients (50.8%) deceased during hospitalization. The patients suffered SCA during non-stressful daily activities (41.4%), while working (14.7%), exercising (12.0%) or resting (8.9%). Patients experienced SCA most often at home (41.9%), in public (31.9%), at work (14.7%), or in the emergency ambulance (6.3%). Bystander-witnessed cardiac arrest was reported in 80.6% of cases. However, lay resuscitation was performed in only 46.1% of cases. The first-monitored rhythm was most frequently ventricular fibrillation (67.0%), followed by asystole (18.3%), ventricular tachycardia (5.8%), pulseless electrical activity (5.2%) and bradycardia (2.1%). Conclusion Compared to other studies, we detected lower rates of SCA occurring at home and higher rates in public, at work or during sports. This may be related to the fact that only younger patients under the age of 65 were included in this SCA cohort.
Gesehen am 12.06.2025